Pengendalian nyamuk Aedes aegypti dengan spray serai alami di Desa Gemawang - Muhamad, Farezki; Nur, Muhammad Adiv Anas; Khomsiana, Yeni Aqnes; Novia, Syakila Ana Sajidah Putri; Citrawati, Dewi; Ulfa, Helya Cholifatul; Ulinuha, Mohammad; Disma, Amanda Fatma Putri; Sasmita, Nanda Yulia; Adilla, Nia; Alfiana, Elsa Wahyu; Setyaningsih, Ayu; Herlyana, Yuniar; Kahayani, Zahra; Ilham, Ahmad; Qori’nurrahman, Faqihana Ananda (Universitas Mataram, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health issue in Indonesia, particularly in areas like Gemawang Village, Temanggung Regency. Chemical insecticides commonly used for mosquito control pose health and environmental risks, necessitating safer alternatives. This study aimed to empower the local community with knowledge and skills to produce a natural mosquito repellent spray using lemongrass (Cymbopogon citratus), which contains citronella and geraniol known for their mosquito-repelling properties. Through a three-month community engagement program, residents participated in educational sessions, practical demonstrations, and were provided with materials to create the spray using lemongrass and 70% ethanol. A total of 100 participants showed a 30% increase in knowledge based on pre-test and post-test results. Additionally, 80% of participants reported regular use of the spray, and 70% observed a decrease in mosquito presence. While participants found the method practical and materials accessible, some noted reduced spray effectiveness over time, indicating a need for improved formulation. This community-based approach not only promoted an eco-friendly alternative to chemical insecticides but also enhanced local capacity for disease prevention. The findings suggest that such participatory programs can contribute significantly to sustainable dengue vector control in endemic areas.